Body image dissatisfaction is associated with perceived body weight among secondary school adolescents in Harar Town, eastern Ethiopia - Tekola, Abainash; Regassa, Lemma Demissie; Mandefro, Miheret; Shawel, Samrawit; Kassa, Obsan; Shasho, Feyisa; Demis, Teshome; Masrie, Awoke; Tamire, Aklilu; Roba, Kedir Teji (Frontiers in Psychiatry, 2024)
Purpose: Body image dissatisfaction has emerged as an important determinant of dietary and physical activity, which in turn determine adolescents' nutritional status. Hence, it is important to understand predictors of body image dissatisfaction. Therefore, this study aimed to assess body image dissatisfaction and its associated factors among secondary school adolescents in the study area.Methods: Data collected for other purposes were used to assess body image dissatisfaction among adolescents in Harar town. Body image dissatisfaction was assessed using the Body Part Satisfaction Scale. Data processing and analysis were performed using STATA version 14, and binary logistic regression was used to identify factors associated with body image dissatisfaction.Factors associated with body image dissatisfaction were determined by estimating AOR along with 95% CI and the statistical significance was declared at a p-value less than or equal to 0.05.The prevalence of body image dissatisfaction was 22.06% [95% CI (19.63, 24.70)]. This study also revealed that males were more dissatisfied with their upper torso and face, and females were more dissatisfied with their middle torso, lower torso, height, and weight than males. In this study, body image dissatisfaction was associated with perception of being fat [AOR = 1.89, 95% CI (1.23, 2.91)], anxiety [AOR = 1.59, 95% CI (1.02, 2.48)], and cigarette smoking [AOR = 1.63, 95% CI (1.03, 2.58)].Almost one in five secondary school adolescents in Harar had body image dissatisfaction, which was significantly associated with perceptions of being fat, anxiety, and smoking. In this study, a significant number of the adolescents experienced body image dissatisfaction. Hence, all concerned bodies have to take action to reduce the burden